Integrative processing of text and multiple maps in multimedia learning: an eye-tracking study - Aiko Morita; Izumi Fukuya (Frontiers in Psychology)
The present study aims to improve understanding of how learners pay attention to the simultaneous presentation of text and multiple pictures in multimedia learning, focusing on the relationship between learners’ reading strategies and learning performance. Specifically, we focused on multiple thematic maps because they should be compared to each other to understand the causal relationships. Thirty-six university students read fictitious geographic learning materials consisting of text and five thematic maps, and completed retention and comprehension tests. Learners’ eye movements were recorded and their relationships with learning outcomes were examined. First, we found that fixation duration on maps was positively correlated with comprehension test scores. Second, the longer fixation duration of high-performance learners begin at an early stage of learning. Third, the gaze shift frequency between maps was positively correlated with comprehension test scores. This study demonstrates that the reading strategy of paying attention to maps and comparing them frequently is associated with higher geographic comprehension.